The effect of virtual reality applications on student achievement in social studies - Salur, Murat; Arikan, Irfan (Routledge Journals, Taylor & Francis Ltd, 2025)
The purpose of the current study is to investigate the effects of virtual reality applications on student achievement in the learning field of People, Places and Environments in the fifth-grade social studies classes. In the study, a quasi-experimental pretest and post-test control group design, one of the quantitative research methods, was employed. As the data collection tool, the People, Places and Environments Achievement Test was used. The collected data were analyzed in the SPSS 22 statistical software program. As a result of the independent samples t-test conducted to test whether there was a significant difference between the mean scores of the experimental and control groups, a significant difference was found between the mean scores of the experimental group (X (sic)=14.18) and the control group (X (sic)=5.35) in favor of the experimental group (t(87)=10.73, p < .05).
Keywords: Achievement; experimental model; social studies; virtual reality